(untitled) - Nelson, Marilyn McCord (California, 1991)
What can you do with a neural network; Next questions: what and why; A brief of neural networks; How do neural networks work; What are neural networks like; How do neural networks relate to other technologies; How many ways can you organize a neural network...
Keywords: Neural networks ( computer science )